2018
DOI: 10.1016/j.phrs.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of oncogenic transcription factors by natural products in eye cancer

Abstract: Carcinogenesis has a multifactorial etiology, and the underlying molecular pathogenesis is still not entirely understood, especially for eye cancers. Primary malignant intraocular neoplasms are relatively rare, but delayed detection and inappropriate management contribute to poor outcomes. Conventional treatment, such as orbital exenteration, chemotherapy, or radiotherapy, alone results in high mortality for many of these malignancies. Recent sequential multimodal therapy with a combination of high-dose chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…In the last two decades, numerous pre-clinical studies have documented the anti-proliferative activity of flavonoids, which has been largely linked to their abilities to interact with specific intracellular signalling pathways, in addition to their well-known antioxidant capacity (57,(59)(60)(61)(62)(63)(64). In this field, recently, we have reported the anti-cancer activity of Citrus bergamia (bergamot) juice (BJ) in different in vitro (65,66) and in vivo (67) models, and have proposed that its flavonoid content is responsible for this action (68).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, numerous pre-clinical studies have documented the anti-proliferative activity of flavonoids, which has been largely linked to their abilities to interact with specific intracellular signalling pathways, in addition to their well-known antioxidant capacity (57,(59)(60)(61)(62)(63)(64). In this field, recently, we have reported the anti-cancer activity of Citrus bergamia (bergamot) juice (BJ) in different in vitro (65,66) and in vivo (67) models, and have proposed that its flavonoid content is responsible for this action (68).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism-informed phenotypic screening is one of the newer strategies for antibacterial HTS assays, the most common of which is a reporter gene assay that reports the signaling pathways with which the hits are interacting [ 35 , 36 ]. However, a reporter gene assay demonstrates if a molecule is working against a specific pathway for which the molecular target needs to be known, which can have spatial and structural differences from strain to strain [ 37 ].…”
Section: Approaches and Strategies For Antibacterial High-throughput ...mentioning
confidence: 99%
“…While primary intraocular cancers are relatively rare diseases, delayed diagnosis and inadequate therapy result in a poor prognosis, and the condition can be fatal if left untreated. Eye cancers, as well as carcinogenesis, have a multifactorial etiology, and a complex molecular pathogenesis that remains unclear [34]. Nevertheless, MMPs, especially the gelatinases MMP-2 and MMP-9, have a significant role in the development and progression of cancers, including those of the colon, lung, prostate, and breast.…”
Section: Ocular Cancersmentioning
confidence: 99%
“…One of the most common intraocular cancers in adults is uveal melanoma (UM), which forms from neuroectodermal melanocytes in the choroid, ciliary body, and iris. Moreover, metastases in the liver are often detected in the course of UM [34]. Its development may be strongly influenced by MMP and TIMP levels: Immunohistochemical studies have found MMP-1, -2, -9, and -19, membrane-type 1-MMP and physiological inhibitors of MMPs (TIMP-2 and -3) to have a heterogeneous distribution and intensity consistent with regional differences in the tumor microenvironment [36].…”
Section: Uveal Melanomamentioning
confidence: 99%